'It is suicide to be abroad. But what it is to be at home …': Beckett as national performance. Issue 1 (1st December 2020) - Lonergan, Patrick
This article explores how nations such as Ireland interact with each other ‐ and seek to understand themselves ‐ by appropriating theatre-makers and other artists, using them to perform versions of that nation to the outside world. This topic is considered through an exploration of the Irish state's appropriation of Samuel Beckett as an icon that represents positive images of Irishness both within and beyond Ireland. This process is explored from shortly after Beckett's death in 1989 to the launch in 2012 of an Irish navy vessel named the LÉ Samuel Beckett. The treatment of Beckett during that period is considered in the context of a broader discussion of nation-branding in Ireland. This is presented in an outline history of the Irish state's performance of itself through its artists, which are discussed in relation to the appearance of Irish writers on banknotes during the twentieth century, among other brief examples related to the work of W. B. Yeats and James Joyce. The article concludes by considering some of the methodological challenges that arise in an investigation of national performance.